BestL1-approximations of classes W_1^r by Splines from W_1^r - Babenko, V. F. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We obtain the exact values of the best L_1-approximations of the classes W_1^r of periodic functions by periodic polynomial splines of degree r and defect 1 with equidistant knots that belong to the class W_1^r.